The quality of life of disabled athletes in terms of socio–cultural issues - sociological approach - Niedbalski, Jakub (Quality in Sport, 2016)
The main objective of the paper is to present the individual, social and organizational determinants of sport for people with disabilities from a sociological perspective. In the article I explained how professional sports can affect the lives of disabled physically people. I focused on the multi-dimensional socio-cultural context. Referring to the individual experience of disabled athletes and the people around them, I have reconstructed the character and scope of the impact of physical activity and sport in the life of disabled person. The article based on a synthesis of three levels: general social, local and individual, which can be distinguished on the basis of research and analysis of empirical material. The conclusions are based on qualitative data gained using unstructured interviews and observation techniques. Analysis and interpretation of the empirical material is carried out according to the methodology of grounded theory.